2020
DOI: 10.3389/fncel.2020.00260
|View full text |Cite
|
Sign up to set email alerts
|

Progranulin Administration Attenuates β-Amyloid Deposition in the Hippocampus of 5xFAD Mice Through Modulating BACE1 Expression and Microglial Phagocytosis

Abstract: Loss of function mutations in the progranulin (PGRN) gene is a risk factor for Alzheimer's disease (AD). Previous works reported that the deficiency of PGRN accelerates βamyloid (Aβ) accumulation in AD transgenic mouse brains while overexpression of PGRN could restrain disease progression. However, mechanisms of PGRN in protecting against Aβ deposition remains unclear. Here, using the 5xFAD AD mouse model, we show that intrahippocampal injection of PGRN protein leads to a reduction of Aβ plaques, downregulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 46 publications
1
14
0
Order By: Relevance
“…Microglial-specific reduction in PGRN expression has been shown to result in impaired phagocytosis, increased plaque load, and exacerbated cognitive deficits in the mouse AD models, whereas lentivirus-mediated PGRN overexpression has opposite results (Minami et al, 2014). Consistent with this result, lentivirus mediated PGRN overexpression or intrahippocampal injection of PGRN protein has been shown to reduce Aβ plaques via increasing the activity of neprilysin, a key amyloid β-degrading enzyme (Van Kampen & Kay, 2017) or through inhibiting the expression of BACE1, an enzyme involved in Aβ generation (Guan et al, 2020). However, another study has found significantly reduced diffuse Aβ plaque growth in hippocampus and cortex in aged PGRN-deficient mice using the APPswe/PS1ΔE9 (APP/PS1) mouse model (Takahashi et al, 2017).…”
Section: Introductionmentioning
confidence: 79%
“…Microglial-specific reduction in PGRN expression has been shown to result in impaired phagocytosis, increased plaque load, and exacerbated cognitive deficits in the mouse AD models, whereas lentivirus-mediated PGRN overexpression has opposite results (Minami et al, 2014). Consistent with this result, lentivirus mediated PGRN overexpression or intrahippocampal injection of PGRN protein has been shown to reduce Aβ plaques via increasing the activity of neprilysin, a key amyloid β-degrading enzyme (Van Kampen & Kay, 2017) or through inhibiting the expression of BACE1, an enzyme involved in Aβ generation (Guan et al, 2020). However, another study has found significantly reduced diffuse Aβ plaque growth in hippocampus and cortex in aged PGRN-deficient mice using the APPswe/PS1ΔE9 (APP/PS1) mouse model (Takahashi et al, 2017).…”
Section: Introductionmentioning
confidence: 79%
“…Loss function mutations in PGRN are considered to be a risk factor for AD [ 47 ]. Previous research on the effect of PGRN on β-amyloid deposition is inconsistent [ 48 , 49 , 50 ]. In the current study, we found that β-amyloid is mainly deposited in the midbrain of Grn −/− mice, which was not observed in the age-matched WT mice ( Figure 7 ).…”
Section: Resultsmentioning
confidence: 99%
“…Little was previously known about the role of PGRN in the nervous system, but since the discovery of PGRN genetic polymorphisms, the number of studies on the role of PGRN in the brain has increased rapidly. Studies have found that PGRN can activate microglia cells and stimulate them to engulf the toxic Aβ around them, which exerts neuroprotective effects [23]. Other studies have found that the content of PGRN in microglia cells which are around Aβ deposits increases in mice [24].…”
Section: Discussionmentioning
confidence: 99%